Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Join our Q&A platform and get accurate answers to all your questions from professionals across multiple disciplines. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

7 5/6 - 1 1/6 - 2 2/3 =

Sagot :

Answer:

4

Step-by-step explanation:

That's the answe!!

Answer:

4

Step-by-step explanation:

7 5/6 - 1 1/6 - 2 2/3 =

= 7 5/6 - 1 1/6 - 2 4/6

= (7 + 5/6) - (1 + 1/6) - (2 + 4/6)

= 7 + 5/6 - 1 - 1/6 - 2 - 4/6

= (7 - 1 - 2) + (5/6 - 1/6 - 4/6)

= 4 + 0/6

= 4